Physiotherapy Practice postoperative blepharoplasty: experimental study - Silveira, Taís Ingrid de Lima; Silva, Rodrigo Marcel Valentim da; Neto, Luis Gonzaga Araújo; Fernades, Ruth Gabryella Praxedes; Meyer, Patrícia Froes (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Blepharoplasty word is of Greek origin (blepharos refers to the eyelids, and plasty is on the form, shape), used to call the eyelid rejuvenation surgery. The physical therapy can prevent or reduce many of the complications caused by blepharoplasty, such as swelling, bruising, hematoma, keloid, among others. Objective: This project aims to observe the physiotherapy performance in the post-blepharoplasty, assessing the general condition of the patient, as the possible complications of surgery. Methods: This study is characterized as a clinical trial and quasi-experimental. The survey sample contains 8 participants (n = 8). Inclusion criteria were patients who had undergone blepharoplasty surgery at the Institute of Vision, female, with a mean age of 60.1 years, menopausal and time availability in the morning and / or afternoon. Exclusion criteria were patients who missed 3 or more sessions, presence of eye diseases such as conjunctivitis, exacerbated pain in the surgery area, infection in the incision area and to provide dehiscence. They started treatment in the second postoperative day, being applied to pumping technique with the use of gauze on the upper eyelid region, manual lymphatic drainage (MLD) and kinesiotherapy in a 40 minute session, with the total of 10 sessions. Results: The level of education of patients and their professions was observed to changes in the postoperative period, the quality of life of patients and duration of the presence of complications. Conclusion: It is suggested that physical therapy in the daily early postoperative period of blepharoplasty may have contributed to avoid complications and that blepharoplasty does not affect the quality of life.